Determinations of millennial impulse online purchase decision: a case of UiTM Kampus Melaka student’s / Muhammad Nur Akmal Bachok @ Akib - Bachok @ Akib, Muhammad Nur Akmal (Faculty of Business and Management, 2018)
The purpose of this study was to determine the factor influencing customer purchasing decision through online shopping in Malaysia. The variables consist of promotion, product feature and website application. The respondents were 77 millennial student in University Teknologi Mara (UiTM) Kampus Bandaraya Melaka. The finding showed that promotion, product feature and website application have influence on the online purchasing decision through online shopping in Malaysia. All variables show significance relationship towards the determinations od millennial impulse online purchase decision in UiTM Kampus Melaka student’s.